2023
DOI: 10.1177/1321103x221139992
|View full text |Cite
|
Sign up to set email alerts
|

Preschool teachers’ music-specific professional development preferences: Does teaching experience matter?

Abstract: The purpose of this study was to investigate Hong Kong preschool teachers’ music-specific professional development (PD) preferences and analyze the potential differences among teachers with varying levels of teaching experience (beginning, experienced, and advanced). A survey was developed to assess four music-specific PD preferences: content, facilitators, types, and activities/resources. We found that respondents ( N = 1,019) preferred PD that was centered on musical creativity and curriculum integration; fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Consequently, teachers lacked confidence in teaching music to children, and their competence was limited. Wong et al (2023) emphasized that teaching experience was a significant factor in determining early childhood teachers' preferences for professional development in music. They found that teachers preferred professional development activities led by music educators, which integrated pedagogy and domain knowledge, focusing on musical creativity.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, teachers lacked confidence in teaching music to children, and their competence was limited. Wong et al (2023) emphasized that teaching experience was a significant factor in determining early childhood teachers' preferences for professional development in music. They found that teachers preferred professional development activities led by music educators, which integrated pedagogy and domain knowledge, focusing on musical creativity.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the efficacy of classroom musical activities, it is vital to provide teachers with training emphasizing music's value in children's development. Additionally, teachers should be equipped with practical and effective strategies that enable them to integrate music into their educational activities (Wong et al, 2023). Moreover, schools should encourage collaboration between teachers and parents to promote music education (Baker, 2012).…”
Section: ⅴ Conclusionmentioning
confidence: 99%